Design and Implementation of Centralized Loan Origination System with Agile Development Method - Sudianjaya, Nella Rosa; Yuhana, Umi Laili (IPTEK The Journal for Technology and Science, 2025)
Credit is a core business with the biggest income in the banking industry. Hundreds of customers come to the bank daily to get loan applications. Because there are a lot of customers, the loan application process can take a whole week, and some customers who can’t wait too long go and come to another bank that can provide a quick loan application process. This paper proposes an application called the Loan Origination System that can facilitate the loan application process. Loan Origination System is expected to handle the loan application process from start to finish, including credit verification, risk analysis, document management, and loan processing. Agile methodology is used in developing a Loan Origination System. Agile methodology is expected to be quick and simple and have more iterative development cycles. The proposed method has been tested using functional suitability results combined with Goal Question Metrics consisting of functional appropriateness, functional correctness, and functional suitability compliances. It gets results with 83.02%, 86.43%, and 85.96%, respectively, for functional appropriateness, functional correctness, and functional suitability compliances. The result shows that the Loan Origination System application meets the requirements and is functionally suitable. The result shows that agile methodology gives the application high flexibility and adaptability, so it is possible to make changes and adjustments in a short time. The application is suitable for helping users process and review the loan application. The application is also user-friendly and, time by time can replace the manual processing of loan applications.